Effectiveness of acoustic cameras as tools for assessing biogenic structures formed by Sabellaria in highly turbid environments. Issue 6 (6th March 2020) - Griffin, Ross A.; Jones, Robyn E.; Lough, Natasha E.L.; Lindenbaum, Charles P.; Alvarez, Maria C.; Clark, Katie A.J.; Griffiths, Jonathan D.; Clabburn, Peter A.T.
Abstract: Accurately mapping the extent and status of biogenic reefs formed by polychaete worms of the genus Sabellaria is of conservation importance given their protected status across Europe. Traditionally, side‐scan sonar (SSS) combined with ground‐truthing in the form of seabed photography and videography has been widely accepted as the most suitable approach for mapping these reefs in the subtidal zone. In highly turbid environments visibility at the seabed can be near zero, however, rendering optical‐based ground‐truthing redundant. Consequently, the true distribution and status of Sabellaria reefs in some shallow subtidal areas around the UK remains unclear despite their designation as Annex‐I features of several Special Areas of Conservation (SACs) under the Habitats Directive. Acoustic camera imagery (ACI) collected using acoustic cameras in two deployment configurations matched well with the backscatter signatures of seabed features in corresponding SSS data. The ACI was of suitable resolution for visualizing Sabellaria colony structures, allowing for their Annex‐I 'reef' defining attributes (extent, patchiness, and elevation) to be assessed. Colony formation 'type' was also distinguishable in the ACI, although confidence in differentiating between low‐lying Sabellaria formations and surrounding substrates was low, particularly when using a pole‐mounted configuration. This study provides a proof of concept for using acoustic cameras as tools for ground‐truthing SSS interpretation and assessing the status of Sabellaria bioconstructions in low‐visibility environments. Further development of this approach and incorporating it into statutory monitoring programmes could improve the management of the reef habitats in subtidal areas of the Severn Estuary and other highly turbid environments.